2018
DOI: 10.1002/cpe.4877
|View full text |Cite
|
Sign up to set email alerts
|

The network structure of Chinese finance market through the method of complex network and random matrix theory

Abstract: Summary As we know, economic policy has a significant influence on the stock market. So, it should be interesting to detect the relation between the correlation structure of the stock market and economic policy. To achieve this target, the correlation matrix is analyzed through component analysis method first, to detect the economic implication of the components of correlation matrix. It is found that the biggest driving force of market behavior affects the whole stock market instead of individual stock or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Several cleaning methods for correlation matrices have been investigated by Bun et al 25 In a different approach, a study focusing on the Korean Stock market have investigated the effect of foreign exchange on the correlations and found that certain sectors showed different behavior than others when their prices converted into Korean Won and US Dollar 26 . In another different setup, Ji et al 27 investigated the relation between the correlation of the Chinese stock market and economic policy. The RMT is not only used for the stock markets but other financial entities.…”
Section: Introductionmentioning
confidence: 99%
“…Several cleaning methods for correlation matrices have been investigated by Bun et al 25 In a different approach, a study focusing on the Korean Stock market have investigated the effect of foreign exchange on the correlations and found that certain sectors showed different behavior than others when their prices converted into Korean Won and US Dollar 26 . In another different setup, Ji et al 27 investigated the relation between the correlation of the Chinese stock market and economic policy. The RMT is not only used for the stock markets but other financial entities.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, these systems have various properties, including nonlinearity and collective behavior. Therefore, the study of an entity alone will not be helpful and the whole system must be analyzed collectively [4][5][6][7][8][9]. A notable feature of these systems is the spatial and temporal dependence of their components [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of 2020, the outbreak of COVID-19 caused global panic. It is reported by WHO that up to September 1st, 2020, there have been 25,327,098 confirmed cases of COVID-19, including 848,255 deaths globally. Since the outbreak of COVID-19, in order to effectively curb the spread of the pandemic, many countries have implemented a series of necessary measures, including shutdown of the production and business and home isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly analyzing the interdependence structure of the stock market is not only of great significance for investors to diversify investment and build investment portfolios during the pandemic, but also is conducive to risk management of the financial market by the regulatory authorities. In recent years, there has been a certain amount of researches on the subject of interdependence among stock markets [18][19][20][21][22][23][24][25]; in these studies, GARCH model, Copula model, Granger causality test, DCC model, and other methods are used to study the interdependence structure between various stock sectors in different countries.…”
Section: Introductionmentioning
confidence: 99%